JENIS-JENIS DAN KARAKTERISTIK BURUNG YANG DITEMUKAN DI KAWASAN BEDUGUL DAN SEKITARNYA - N. N. Wirasiti; N. M. Rai Suarni; A. A. G. Raka Dalem (Bumi Lestari Journal of Environment)
A study on birds (species and their characteristics) was carried out in Bedugul(Bali) between November and December 2004. Observation was made along transectlines which are set prior to the study. Species of birds observed were identified andrecorded. In addition, their distributions, status, source of food, reproductive seasons, aswell as migration patterns (whether migrant species or not) were determined. Thisstandard sampling strategy was also supported by casual observation and interview.Results of this study showed that Bedugul and surrounding area have a significantrole in conservation of Bali birds, because at least 56 species of birds have beenidentified in this area, which comprises of 18% of Bali birds. Conservation priorityshould be put on 8 species (14%) of the birds which are protected by law, as well as on 7% of endemic species (for Java and Bali). In addition, conservation effort should be alsogiven priority to 9% of birds that considered to be rare and potentially that be locallyextict. Habitat conservation should becoming focus of attention since it determines theavailability of food sources for those birds. Conservation on forest, plantation as well asshrubs should become focus of attention since these become habitats of more than a half(57%) of birds available in this area.